2020
DOI: 10.3389/fneur.2020.582388
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Occlusion Type and Etiology of Acute Intracranial Large Artery Occlusion

Abstract: Objective: To investigate the diagnostic efficiency of truncal-type occlusion and branching-site occlusion in determining the etiology of intracranial large artery occlusion related acute ischemic stroke (AIS). Methods: Patients with intracranial large artery occlusion related AIS who received stent retriever (SR) thrombectomy from November 2014 to June 2019 were included in the study. All patients underwent angiography before SR thrombectomy, which was used to evaluate the occlusion type. Differences in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Previous studies have correlated the angiographic occlusion type with the etiology. They found that truncal-type occlusion usually originated from atherosclerosis in large intracranial arteries, whereas branchingsite occlusion is mostly due to cardiogenic embolism, lodged in the sharp turns of the bifurcation of a vessel (5,11). One of the reasons of this is that cardiogenic thrombi seemed to have a higher proportion of fibrin compared to other stroke etiologies, making it associated with worse interventional recanalization (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have correlated the angiographic occlusion type with the etiology. They found that truncal-type occlusion usually originated from atherosclerosis in large intracranial arteries, whereas branchingsite occlusion is mostly due to cardiogenic embolism, lodged in the sharp turns of the bifurcation of a vessel (5,11). One of the reasons of this is that cardiogenic thrombi seemed to have a higher proportion of fibrin compared to other stroke etiologies, making it associated with worse interventional recanalization (24).…”
Section: Discussionmentioning
confidence: 99%
“…The occlusion was defined as a branching-site occlusion when (1) contralateral ICA flow could not further advance across the relevant ICA bifurcation site, (2) Y-or T-shaped filling defect involving branching site is directly observed, or (3) another branch could not be seen even on stent-retriever deployment to one branch across occlusion site. Conversely, the occlusion type was classified as truncal-type occlusion when all major branches and relevant bifurcations are clearly observed (5,11).…”
Section: Angiographic Occlusion Type Classificationmentioning
confidence: 99%
“…The ischemic stroke etiology was assessed based on the medical history, clinical features, and DSA results. The identification of ICAS-LVO was primarily based on DSA imaging, including (1) residual stenosis > 70% after first-line thrombectomy; (2) moderate residual stenosis with impairment of distal flow; (3) microcatheter “first-pass” effect during the procedure ( 2 , 12 ). Then, patients were divided into two groups: ICAS-LVO and non-ICAS-LVO.…”
Section: Methodsmentioning
confidence: 99%
“…Several large-scale randomized controlled trials have demonstrated that endovascular thrombectomy can effectively treat large vascular occlusion (LVO) ( 1 ). Intracranial atherosclerosis (ICAS)-related LVO (ICAS-LVO) is a major etiology of LVO, especially in Asian populations ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses and predictions of occlusion types have been investigated in previous studies ( 12 , 13 ). However, these studies usually rely heavily on digital subtraction angiography (DSA) characteristics, which seems lagging in predicting models.…”
Section: Introductionmentioning
confidence: 99%